Perioperative frozen section examination in parotid gland tumors - Carvalho, Marcos Brasilino de (1999)
CONTEXT: The minimal recommended surgical approach to parotid tumors is partial parotidectomy with resection of the superficial lobe of the gland. Histologic diagnosis prior to surgery is not possible, as incisional biopsies are contraindicated due to the possibility of facial nerve injury or incomplete tumor resection. Thus, the biopsies tend to be perioperative. OBJECTIVE: To compare the results of frozen section examination with the definitive pathological diagnosis. DESIGN: Accuracy study by retrospective analysis. SETTING: Head and Neck Surgery Service of Heliópolis Hospital, São Paulo, Brazil. SAMPLE: 153 cases of parotid gland tumors treated between 1977 and 1994. DIAGNOSTIC TEST: Frozen section and pathological diagnosis. MAIN MEASUREMENTS: Sensibility and specificity of the frozen section examination. RESULTS: Frozen section study diagnosed 19 (12.4%) malignant and 127 (83.7%) benign tumors. Sensitivity of the frozen sections for malignancy was 61.5% (95% CI 54 to 69%) and specificity was 98% (95% CI 94 to 100%), and this result is comparable to the literature. CONCLUSIONS: We consider that frozen section examination for salivary gland tumors is not sufficient on its own for deciding on the best management. Their interpretation must be correlated with clinical and intraoperative findings, in association with the surgeon's experience.